Bioactive glass added to autogenous bone graft in maxillary sinus augmentation: a prospective histomorphometric, immunohistochemical, and bone graft resorption assessment - Juliana Dreyer MENEZES; Rodrigo dos Santos PEREIRA; João Paulo BONARDI; Geraldo Luiz GRIZA; Roberta OKAMOTO; Eduardo HOCHULI-VIEIRA (University of São Paulo, 2018)
Abstract Objective The aim of this study was to compare the bone resorption rate, histomorphometry and immunohistochemical findings of bioactive glass (Biogran; Biomet, Warsaw, IN, USA) mixed with autogenous bone grafts (1:1) and autogenous bone graft isolate in maxillary sinus elevation surgery. Material and Methods A total of 9 maxillary sinuses were grafted with Biogran with autogenous bone graft (group 1) and 12 were mixed with autogenous bone graft (group 2). Postoperative cone beam computed tomography (CBCT) was used to measure the initial graft volume after 15 days (T1), and 6 months later, another CBCT scan was performed to evaluate the final graft volume (T2) and determine the graft resorption rate. The resorption outcomes were 37.9%±18.9% in group 1 and 45.7%±18.5% in group 2 (P=0.82). After 6 months, biopsies were obtained concurrent with the placement of dental implants; these implants were subjected to histomorphometric analysis and immunohistochemical analysis for tartrate-resistant acid phosphatase (TRAP). Results The average bone formation in group 1 was 36.6%±12.9 in the pristine bone region, 33.2%±13.3 in the intermediate region, and 45.8%±13.8 in the apical region; in group 2, the values were 34.4%±14.4, 35.0%±13.9, and 42.0%±16.6 of new bone formation in the pristine bone, intermediate, and apical regions, respectively. Immunostaining for TRAP showed poor clastic activity in both groups, which can indicate that those were in the remodeling phase. Conclusions The similarity between the groups in the formation and maintenance of the graft volume after 6 months suggests that the bioactive glass mixed with autogenous bone (1:1) can be used safely as a bone substitute for the maxillary sinus lift.